Terapi Pijat dalam Penanganan Spastisitas Hemiparesis Ekstremitas Atas pada Pasien Stroke - Sinyo Pelani; Agianto Agianto; Rismia Agustina (FORIKES, 2022)
Spasticity is a symptom of stroke which can lead to weakness and disability. A series of recovery can be done, one of which is using massage therapy. Massage differs in the type of procedure, duration of administration, duration of disease onset, and effectiveness. So it is necessary to do a literature study that aims to determine the effectiveness of massage therapy in the treatment of upper extremity hemiparesis spasticity in stroke patients. This literature review searches for articles 2000-2020 in Indonesian and English, from Pubmed, Science Direct, and Google Scholar. Assessment of article quality using JBI's Critical Appraisal Tools. Data synthesis in narrative form. The results of the study obtained 4 synthesized articles. Tuina can be given without or in addition to other interventions. Tuina is effective for reducing upper extremity muscle spasticity at disease onset 1-3 months. It was concluded that Tuina was effective in reducing upper extremity spasticity and could be given to post-stroke patients 1-3 months.Keywords: massage; spasticity; strokesABSTRAK Spastisitas merupakan gejala stroke yang dapat mengakibatkan kelemahan dan kecacatan. Serangkaian pemulihan dapat dilakukan, salah satunya adalah menggunakan terapi pijat. Pemijatan memiliki perbedaan dalam jenis prosedur, durasi pemberian, lama onset penyakit, dan keefektivitasannya. Maka perlu dilakukan studi literatur yang bertujuan untuk mengetahui efektivitas terapi pijat pada penanganan spastisitas hemiparesis ekstremitas atas pada pasien stroke. Tinjauan literatur ini mencari artikel tahun 2000-2020 dalam Bahasa Indonesia dan Bahasa Inggris, dari Pubmed, Science Direct, dan Google Scholar. Penilaian kualitas artikel menggunakan JBI’s Critical Apraisal Tools. Sintesis data dalam bentuk naratif. Hasil studi memperoleh 4 artikel yang disintesis. Tuina dapat diberikan tanpa atau dengan tambahan intervensi lain. Tuina efektif untuk menurunkan spastisitas otot ekstremitas atas pada onset penyakit 1-3 bulan. Disimpulkan bahwa Tuina efektif untuk menurunkan spastisitas ekstremitas atas dan dapat diberikan pada pasien pasca stroke 1-3 bulan.Kata kunci: pijat; spastisitas; stroke